The budgetary role of the Indonesian parliament: The impact of the law on state finances - Emirullah, Chandra (2013)
The role of Parliament in budget process in an important issue in public financial management. The extent the Parliament exercises control in determining budget appropriations affects the flexibility of spending units in utilizing their budget optimally.This paper looks at the budgetary role of the Indonesian Parliament in implementing the Law on State Finance enacted in 2003. This paper shows that the law's requirement that the appropriation of annual budget is provided at the detailed activity level is not supportive of the government goal to reduce corruption and leads to undue disbursement delays. The resulting budget rigidity is also not supportive of the government on increase efficiency and effectiveness in financial management through Performance-Based Budgeting and MTEF.